MENINGKATKAN PENGETAHUAN MATEMATIKA DALAM BIDANG PENGEMBANGAN KOGNITIF MELALUI KEGIATAN BERMAIN - Norma Sulistiyani; Usman Afdal; Sitti Nurhidayah Ilyas; Yuliani; St. Aisyah Syahrani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
Math play is a learning activity that can develop children's basic cognitive math skills in the early stages. In addition, math play is also able to improve children's cognitive abilities in solving problems, as well as the ability to measure / estimate, know and distinguish space concepts. This study aims to develop children's potential mathematical knowledge through play activities. This research is a classroom action research with a two-cycle work procedure consisting of the stages of planning action, doing, observing and reflecting. The results of the research in cycle I showed that in the first cycle of 15 children, there were 8 children who had not developed (53.3%), 3 children began to develop (20%), 2 children developed as expected (13.3%), and 2 children developed very well (13.3%). Whereas in cycle II it was seen that this activity was greatly improved so that there was no need for repetition of learning again, namely out of 15 children, there were 0 children who had not developed (0%), 1 child began to develop (6.6%), 1 child developed as expected (6.6%), and 13 children developed very well (86.6%). This shows that play activities are able to increase mathematical knowledge in the field of cognitive development